TANGGUNG JAWAB ORANG TUA TERHADAP NAFKAH ANAK PASCA PUTUSAN PERCERAIAN BAGI WARGA NEGARA INDONESIA YANG BERAGAMA ISLAM - Anjani Sipahutar; Tan Kamello; Runtung Runtung; Utary Maharany Barus (Universitas Sumatera Utara, 2016)
ABSTRACT Responsibility is a readiness to accept an obligation or duty. It means that the responsibility is innate and a part of human life, that every human being has his/her own responsibility, there will be somebody else forces him/her to be responsible. It is clear that if a marriage ends with divorced, parents (their family) are responsible to protect their children from any problem related to the presents world or the hereafter. This study was aimed to answer the problem of how Moslem Indonesian divorced parents were responsible for the living of their children, to look at the judge's decision that required a father to continue his responsibility after his divorced was violated, and to find out whether the law in concrete found in the decision of the judge of religious court had been in accordance with the legal norms regulated in the law. Keywords : Responsibility, Divorce, Child Maintenance